The Role of Stereotactic Body Radiation Therapy for Hepatocellular Carcinoma Patients: A Literature Review - Giselvania, Angela; Sekarutami, Sri Mutya; Munandar, Arie; Halim, Devina Adella; Wijovi, Felix (Indonesian Journal of Cancer, 2024)
Background: Globally, hepatocellular carcinoma (HCC) is the most prevalent kind of primary liver cancer. Treatment options for HCC include radiotherapy, immunotherapy, surgery, targeted therapy, transarterial chemoembolization, and hepatic arterial infusion chemotherapy. Limited efficacy was observed since 70-80% of cases are diagnosed late and unresectable. Growing evidence reported that SBRT is a viable option for locoregional treatments like radiofrequency ablation (RFA) or transarterial chemoembolization (TACE) for patients who did not respond to those treatments. Methods: A thorough search of electronic databases including PubMed, Cochrane Library, and Embase was conducted for studies on Stereotactic Body Radiation Therapy for Hepatocellular Carcinoma published in English over the past 10 years. The review process followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to ensure a systematic approach. Inclusion criteria encompassed studies focusing on SBRT use in HCC treatment, with extracted data synthesized to provide a comprehensive overview of current evidence. Any discrepancies during the review were resolved through consultation with a third reviewer when necessary. Results: In comparison to conventional radiation therapy, Stereotactic Body Radiation Therapy (SBRT) offers precise administration of the high dose of radiotherapy, given in fewer fractions, and may be used in conjunction with other therapy modalities. Global guidelines, including in Indonesia, have proposed the implementation of SBRT. Local control was reportedly achieved in around 90–95% of HCC patients. Multimodal therapies, combined with TACE, showed superior results regarding the local control and overall survival. SBRT may eventually become the definitive treatment for early-stage HCC patients and has a critical role as a transitional therapy for patients awaiting liver transplantation. Improved outcomes and quality of life were also observed in patients with portal vein thrombosis (PVT) and extrahepatic metastases who underwent SBRT. Conclusions: SBRT results in promising local control, raises overall survival, and improves the quality of life in HCC patients with various stages.